DIVERSIFIKASI KOMODITAS SAYUR-SAYURAN DALAM MENINGKATAN PENDAPATAN PETANI PERKOTAAN DI KECAMATAN JAMBI SELATAN KOTA JAMBI - Aprollita, Aprollita (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This research was conducted in the Pall Merah Village, Jambi Selatan District, Jambi City, against 38 vegetable farmers who were selected at random. The purpose of this study was to determine the level of diversity of commodities and to determine the effect of vegetable crop diversification on increasing income in Jambi Selatan District, Jambi City. Data will be analyzed qualitatively and quantitatively. Qualitative analysis is used to look at cultivation activities, diversification patterns (diversification) of the business in the vegetable commodities in the study location and several other related matters will be described descriptively. Quantitative analysis is presented in the form of a tabulation which aims to simplify the data in an easy-to-read form. The results of the study show that there are 11 vegetable commodities making up the diversification pattern in South Jambi District consisting of 5 diversified cropping patterns with a moderate diversity index. The highest profit is obtained from cropping pattern V (7 commodities) and with a correlation coefficient between diversity and income of r = 0.805249241, this can be interpreted that the strength of the relationship between variable levels of diversity and income is near perfect.Keywords: vegetables, diversification, income